1992
DOI: 10.3109/00016489209137448
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of a-Atrial Natriuretic Polypeptide in the Rat Cochlea

Abstract: The localization of alpha-atrial natriuretic polypeptide (alpha-ANP) in the rat cochlea was studied by immunohistochemical technique, using a polyclonal antibody against synthetic rat alpha-atrial natriuretic polypeptide (alpha-rANP). The spiral ligament of the lateral cochlear wall exhibited pronounced immunoreactivity to atrial natriuretic polypeptide (ANP), whereas the stria vascularis displayed almost no immunoreaction. ANP immunoreactivity (IR) was also intense in the spiral limbus region. IR was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Furthermore, ANP and its receptors have been found in the CNS, leading us to speculate that ANP may function as a neuromodulator or neuropeptide involved in neuronal and glial functions [34][35][36]. Importantly, their presence in the secretory and sensory compartments of the rodent inner ear is well documented, suggesting ANP may act as a local hormone regulating the fluid and electrolyte balance in the inner ear [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Previous reports revealed that ANP receptors have been localized to the cochlear modiolus of the guinea pig [42] and rat SG [51].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ANP and its receptors have been found in the CNS, leading us to speculate that ANP may function as a neuromodulator or neuropeptide involved in neuronal and glial functions [34][35][36]. Importantly, their presence in the secretory and sensory compartments of the rodent inner ear is well documented, suggesting ANP may act as a local hormone regulating the fluid and electrolyte balance in the inner ear [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Previous reports revealed that ANP receptors have been localized to the cochlear modiolus of the guinea pig [42] and rat SG [51].…”
Section: Introductionmentioning
confidence: 99%
“…ANP in the membranous labyrinth may affect inner ear fluid pressure and fluid and ion transport and indirectly even the neurotransmission in the acoustic nerve [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the ear, ANP may play a role in maintaining water and/or ion homeostasis of the fluids that are responsible for normal hearing. We previously reported that ANP is present in the rat inner ear by immunohistochemical studies 11, 12. Interestingly, ANP immunoreactivity was detected in the spiral ligament and spiral limbus of the rat cochlea.…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies have revealed extra‐atrial ANP in various tissues 3, 7–10. The presence of ANP in the rat inner ear was first described by Yoon and Hellstrom, who have suggested that it may regulate the volume of perilymph 11, 12. Changes in the volume of perilymph may result in stretching of the surrounding wall, thereby stimulating the secretion of ANP.…”
Section: Introductionmentioning
confidence: 99%